2021
DOI: 10.1007/s11695-021-05710-5
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Surgical Weight Reduction on Left Atrial Strain

Abstract: Background Obesity increases and surgical weight reduction decreases the risk of atrial fibrillation (AF) and heart failure (HF). We hypothesized that surgically induced weight loss may favorably affect left atrial (LA) mechanical function measured by longitudinal strain, which has recently emerged as an independent imaging biomarker of increased AF and HF risk. Methods We retrospectively evaluated echocardiograms performed before and 12.2 ± 2.2 months aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…28 Moreover, Strzelczyk et al demonstrated an increase in LARS after bariatric surgery in patients with severe obesity without previous history of cardiac disease or arrhythmia. 29 The moderate correlation between ΔLARS and MAP (and ΔMAP) observed in our study supports previous cross-sectional data demonstrating a link between elevated BP and impaired LARS. 25,30,31 Our results emphasize the importance of managing both BP and weight to hamper the progression of cardiac maladaptation.…”
Section: δLars (%) δLaef (%)supporting
confidence: 91%
“…28 Moreover, Strzelczyk et al demonstrated an increase in LARS after bariatric surgery in patients with severe obesity without previous history of cardiac disease or arrhythmia. 29 The moderate correlation between ΔLARS and MAP (and ΔMAP) observed in our study supports previous cross-sectional data demonstrating a link between elevated BP and impaired LARS. 25,30,31 Our results emphasize the importance of managing both BP and weight to hamper the progression of cardiac maladaptation.…”
Section: δLars (%) δLaef (%)supporting
confidence: 91%
“…Strzelcyk et al observed similar results and reported a significant increase in LASr and LAScd after bariatric surgery, and a decrease in LASct [ 39 ]. The authors explained the decrease in LASct in their study mechanistically as an improvement of early LV diastolic filling that may lead to a relative decrease of the contribution of atrial contraction [ 39 ]. Bariatric surgery leads to complex metabolic and hemodynamic changes.…”
Section: Discussionmentioning
confidence: 69%
“…In this study, LA cavity size followed a similar trajectory to LV cavity size, initially falling in size and then increasing from 212 days onwards. Previous studies have also shown a decrease in LA volume within 1 year of bariatric surgery ( 43 , 44 ), with other studies reporting no change in LA volume after 1 year ( 41 , 45 , 46 ), and increased LA volume after 5 years ( 34 ). Whilst the initial reduction in size follows the reduction in cardiac output, as for the LV, the loss of EAT from the pericardial space may again allow further space for this LA cavity dilation to occur.…”
Section: Discussionmentioning
confidence: 76%